Encyonema appalachianum (Bacillariophyta, Cymbellaceae), a new species from Western Pennsylvania, USA - Potapova, Marina (Phytotaxa, 2014)
A new species of Encyonema was found in several rivers and reservoirs in Western Pennsylvania, USA, in 2013. The new species, E. appalachianum, has only very slightly dorsiventral valves, which is one of the characters separating the genus Encyonopsis from Encyonema. On the other hand, the long, sharply bent terminal raphe fissures and lateral raphe indicate that it should be placed in Encyonema. Some valves with occasionally biseriate striae have been observed in the type population of the new species. The finding of this species that apparently combines features of both Encyonema and Encyonopsis highlights the problem of poorly defined boundaries between some genera of cymbelloid diatoms.